Air pollution: the process of PM2.5 ingestion into the body and its impact on health - Rangga, Josfirin Uding (Environmental and Toxicology Management, 2024)
PM2.5 consists of fine particles with a size of less than 2.5 micrometers, which can be easily inhaled and enter the respiratory tract, causing various health problems. Transportation plays a major role in increasing PM2.5 levels in urban areas. Some things that can be done to minimize the impact of PM2.5 are the establishment of strict air quality standards, the development of environmentally friendly technologies for industry and transportation, and increasing public awareness of the impact of air pollution on health. In addition, government policies are also needed such as the use of public transportation and greening. So that the negative impact of PM2.5 on health can be minimized and air quality can be significantly improved.